The wellbeing of infants exposed to Buprenorphine via breast milk at 4 weeks of age - Gower, Shelley; Bartu, Anne; Ilett, K.; Doherty, D.; McLaurin, R.; Hamilton, D. (Sage Science Press, 2014)
Background: Buprenorphine has been available in Australia since 2000 as an alternative pharmacotherapy to methadone for the treatment of opioid dependence. However, there is little information in the literature regarding the effect of buprenorphine on the wellbeing of infants exposed to buprenorphine via breast milk, following discharge from hospital. Objective: The aim of the present study was to examine the wellbeing of infants exposed to buprenorphine via breast milk up to 4 weeks postnatal. Methods: Approximately 4 weeks after birth, information on the feeding and sleeping patterns, skin color, infant elimination patterns and hydration, and Neonatal Abstinence Scores of infants (n = 7) exposed to buprenorphine via breast milk was collected via both observation and documentation. Results: Infants were progressing well, with normal sleep patterns and skin color, and 2 mothers had minor concerns regarding infant elimination patterns. Four infants were exclusively breastfed and 3 were receiving a supplement, with a range of 260 to 700 mL of formula over 24 hours. The sleep patterns following feeding ranged from 1.55 to 3.33 hours, with a median of 2.12 hours. Conclusion: No adverse effects were detected in infants exposed to buprenorphine via breast milk up to 4 weeks postnatal. Further research using larger samples to assess possible developmental effects over longer periods of time is required.